Analisis Pengaruh Faktor Kritis pada Keberhasilan Proyek Data Desa Presisi - Raden Rara Indriyati Kusumawardani Mulyoningtyas; Alain Widjanarka Handaka (Research Center and Case Clearing House PPM School of Management, 2022)
The purpose of this study is to reveal the critical factors that influence the success of the Precision Village Data (DDP) project, the critical factors that have the highest effect/ impact on the implementation of the DDP project, and the degree of influence of critical factors on the success of the DDP project. This research uses a quantitative approach supported by qualitative data. The units of analysis in this research are the enumerators, the project team, and the village government involved in the DDP project. The sampling technique used is the census method, with a total of 141 respondents. Collected data was through a questionnaire with a Likert scale, then analyzed by Partial Least Square (PLS). The research was conducted in 6 villages namely Sukamantri Village (Bogor), Tegallalang Village (Gianyar Bali), Cihideung Ilir Village (Bogor), Cibanteng Village (Bogor), Gelar Anyar Village (Cianjur), and Bantar Jaya Village (Bogor). The results of the individual parameter significance test (t-test) show that the project management CSFs and workforce plans have a positive and partially significant effect on the success of the DDP project. Furthermore, the simultaneous test results (F test) show that all the factors in the dimensions of the CSFs have a positive and significant effect on the success of the DDP project simultaneously